Freedom of Religion in Canada – The Principled and the Pragmatic - Moon, Richard (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2023)
While much of Canada’s early commitment to religious freedom was simply a pragmatic compromise to ensure social peace and political stability, the Supreme Court of Canada in a series of judgments that pre-dated the Charter sought to articulate a principled account of religious freedom as an “original freedom” that is an important “mode[] of self-expression” and “the primary condition[] of the community life”. This understanding of religious freedom shaped the Supreme Court of Canada’s initial reading of freedom of conscience and religion protected by s. 2 (a) of the Canadian Charter of Rights and Freedoms. However, the story of religious freedom in Canada is not simply that of a linear progression from the pragmatic tolerance of religious minorities to the principled protection of the individual’s religious freedom. In its subsequent s 2 (a) decisions, the Court began to read freedom of religion as a form of equality right that requires the state to remain neutral in religious matters. The state must not prefer the practices of one religious group over those of another and it must not restrict the religious practices of a group unless it has a substantial public reason to do so. Underlying the Court’s commitment to religious freedom is a recognition of the deep connection between the individual and her/his spiritual commitments and religious community and a desire to avoid the marginalization of minority religious groups. Concerns about inclusion and social peace that lay behind the extension of religious tolerance in Canada’s early history continue to be important in the contemporary justification and interpretation of religious freedom. The Court’s commitment to state neutrality in religious matters requires it to distinguish between the private sphere of individual or group spiritual life and the sphere of public secular life. However, the line between these two spheres is contestable, moveable, and porous.